Parents towards the problem of body posture defects and physical activity of children from grades 1–3 of primary school - Makarczuk, Anna (Physical education, sport and olympism from a pedagogical perspective, 2023)
The aim of the study was to assess the level of knowledge and awareness of parents of children from the first grades of primary school about body static disorders and physical activity. The research was carried out in the years 2017–2019 in Lodz. Parents of children from five primary schools, representing five districts of the city, were subjected to them. The study used the diagnostic survey method. In total, 521 correctly completed questionnaires were obtained. The surveyed parents only in about ⅓ of all cases answered correctly the questions about the characteristics of posture defects and their diagnosis. However, most of them are aware of the importance of physical activity for the proper development of the child and they take care of correcting body posture every day.